Kegiatan Menulis dan Membaca Huruf Hijaiyah dengan Menggunakan Metode Flashcard untuk Meningkatkan Kemampuan Santri di TPQ As-Sabiqun - Yuliastutik Yuliastutik; Zakiya Qothrun Nada; Nadhira Shava Putri Ramadhan (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This study aims to improve the reading and writing skills of early age students in TPQ As-Sabiqun using the flashcard method. Learning the hijaiyah letters is very important in Islamic education because it is the first step to understanding the Qur'an. In implementing this activity, the Participatory Action Research (PAR) approach was used with interview, observation, and documentation methods. The results of the activity showed an increase in students' interest in learning, cognitive abilities, and fine motor skills. Flashcards have proven to be effective as interactive and interesting visual learning media for children. This activity also encourages the formation of religious character from an early age and strengthens the relationship between students and teachers. This study recommends the use of flashcard media as a relevant and educational learning strategy in introducing the hijaiyah letters to children.